2015
DOI: 10.1007/s11270-015-2325-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-Contaminated Water Remediation Supported by Solid Organic Carbon and ZVI-Combined System

Abstract: Solid organic carbon and zero-valent iron (ZVI) have been used separately as reactive media in permeable reactive barriers (PRBs) to degrade nitrate in groundwater, but few studies have examined the combination of the two materials in one system for nitrate remediation. In the present study, batch tests are conducted to evaluate three common solid organic carbons and their combination with ZVI for nitrate removal from water. The results show that the combined system achieves better denitrification efficiency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Chemical denitrification refers to the reduction of nitrate using zero-valent iron (Fe 0 ) due to its high reaction rate (Ao et al 2019). However, ammonia generated by the reduction of nitrate results in secondary pollution in groundwater, and the process of adding Fe 0 is difficult to control (Wang et al 2015;Fageeh et al 2017;Wei et al 2018). In biological denitrification pro-cesses, using organic compounds as electron donors can reduce nitrate to nitrogen gas with higher selectivity and rate, and enhancing denitrifying bacterial activities by adjusting the microbial environment (Fowdar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical denitrification refers to the reduction of nitrate using zero-valent iron (Fe 0 ) due to its high reaction rate (Ao et al 2019). However, ammonia generated by the reduction of nitrate results in secondary pollution in groundwater, and the process of adding Fe 0 is difficult to control (Wang et al 2015;Fageeh et al 2017;Wei et al 2018). In biological denitrification pro-cesses, using organic compounds as electron donors can reduce nitrate to nitrogen gas with higher selectivity and rate, and enhancing denitrifying bacterial activities by adjusting the microbial environment (Fowdar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The organic carbon compounds such as methane (Wang et al 2015), fructose, glucose (Yan et al 2016), methanol, acetic acid, and propionic acid (He et al 2015) have high bioavailability for microorganisms. However, organic carbon compounds are expansive and the implementation process is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various modified Fe 0 by microbes [16], Fe oxides [17], minerals [18] and organic carbon [19] was used to improve the degradation effect of nitrate. It was found that the reductive efficiency of nitrate by Fe 0 increased as the concentration of dissolved ferrous ion (Fe 2+ aq ) increased in solution [20,21].…”
Section: Introductionmentioning
confidence: 99%